Praktik Supervisi Akademik Kepala Sekolah Dan Implikasinya Terhadap Pengembangan Organisasi Sekolah - Sri Astuti Iriyani; Putri Ellen Gracia Risamasu; Rahmania Sadek; Amir Rifa’i; Agus Timan (CV. Global Cendekia Inti, 2026)
Academic supervision plays a strategic role in improving teacher professionalism, learning quality, and school organizational effectiveness. This study aims to analyze the patterns of academic supervision implemented by school principals as a basis for school organizational development. The research approach uses a qualitative method with a descriptive phenomenological study design to explore in depth the experiences and practices of supervision. Data were collected through in-depth interviews and documentation studies involving principals, teachers, and staff at Muhammadiyah Junior High School. Data analysis was conducted interactively through the stages of reduction, presentation, and conclusion drawing by adapting the Input, Process, Output framework. The results showed that academic supervision was carried out collegially and participatively, but not yet structured. The role of the principal as an academic supervisor is not yet optimal, but this condition does not significantly impact the low quality of the learning process. The research findings indicate that this condition is due to the strong professional commitment of teachers and collaborative support among school personnel. These findings emphasize the urgency of strengthening the capacity of principals and developing a more systematic supervision mechanism to support the sustainable development of school organizations.